Subcooled flow boiling of water in a copper microchannel: Experimental investigation and assessment of predictive methods. (April 2019) - Ramesh, Bhaarath; Jayaramu, Prasanna; Gedupudi, Sateesh
Abstract: The current study presents experimental pressure drop and heat transfer data for subcooled flow boiling of water in a 1.0 mm wide × 0.49 mm deep × 40 mm long aged copper microchannel. The experiments were performed for three inlet temperatures: 30 o C, 50 o C and 70 o C, each with mass flux range of 528–1188 kg/m 2  s and heat flux range of 260–1100 kW/m 2 . The trends observed in experimental subcooled boiling heat transfer and pressure drop are reported. The performance of existing predictive methods in predicting pressure drop, heat transfer and boiling incipience is also assessed. The study also evaluates the appropriateness of using singe phase correlations for predicting subcooled boiling pressure drop, a practice which is used in many flow boiling studies, and recommends that the approach be not used for low inlet subcooling.